Democratic transition, The: a study of the causality between income and the Gastil democracy index - Martin Paldam; Erich Gundlach (Kiel Institute for the World Economy (IfW), 2008)
The paper considers the transformation of the political system as countries pass through the Grand Transition from a poor developing country to a wealthy developed country. In the process most countries change from an authoritarian to a democratic political system. This is shown by using the Gastil democracy index from Freedom House. First, the basic pattern of correlations reveals that a good deal of the short- to medium-run causality appears to be from democracy to income. Then a set of extreme biogeographic instruments is used to demonstrate that the long-run causality is from income to democracy. The long-run result survives various robustness tests. We show how the Grand Transition view resolves the seeming contradiction between the long-run and the short- to medium-run effects.
Keywords: B25; O1; 330; Paths of development; democracy; biogeography; Demokratisierung; Entwicklungsstufe; Sozialprodukt; Schätzung; Welt